Membangun Kesadaran Hukum Bagi Siswa di SMA Negeri 4 Gorontalo - Mozin, Nopiana; Lukum, Roni; Ongomai, Sa’ban S. (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Indonesia, as a state governed by law, upholds the supremacy of law, equality before the law, and fair law enforcement as its fundamental pillars. However, legal awareness among teenagers, particularly high school students, remains relatively low, as evidenced by the prevalence of bullying, sexual harassment, and traffic violations. This community service activity aimed to enhance students’ legal awareness through a collaborative program involving lecturers and undergraduate students of the Civic Education Study Program at Universitas Negeri Gorontalo, conducted at SMA Negeri 4 Gorontalo and attended by 30 eleventh-grade students. The method employed was a participatory approach, which included interactive legal socialization, group discussions, case simulations, and reflection activities, with evaluation carried out through pre-tests and post-tests. The results showed a significant increase in legal understanding, a decline in deviant behavioral tendencies, and improved student participation in legal issue discussions. The integration of experiential learning with the active involvement of students as equal facilitators created a more egalitarian and contextual legal learning atmosphere for high school students. Experience-based legal education proved effective in instilling legal awareness at the cognitive, affective, and psychomotor levels. Therefore, fostering legal awareness from an early age through participatory methods can serve as a foundation for shaping law-abiding and integrity-driven youth, while also contributing to the realization of a just and orderly society. The continuity of such programs is highly recommended to ensure the consistent internalization of legal values.ABSTRAKIndonesia sebagai negara hukum menempatkan supremasi hukum, kesetaraan di hadapan hukum, dan penegakan hukum yang adil sebagai pilar utamanya. Namun, kesadaran hukum di kalangan remaja, khususnya siswa SMA, masih tergolong rendah, sebagaimana terlihat dari tingginya kasus bullying, pelecehan seksual, hingga pelanggaran lalu lintas. Pengabdian ini bertujuan untuk meningkatkan kesadaran hukum siswa melalui program kolaboratif dosen dan mahasiswa Prodi S1 PPKn Universitas Negeri Gorontalo yang dilaksanakan di SMA Negeri 4 Gorontalo dan diikuti oleh 30 siswa kelas XI. Metode yang digunakan adalah pendekatan partisipatif, meliputi sosialisasi interaktif, diskusi kelompok, simulasi kasus, dan refleksi, dengan evaluasi melalui pre-test dan post-test. Hasilnya menunjukkan adanya peningkatan signifikan dalam pemahaman hukum, penurunan kecenderungan terhadap perilaku menyimpang, serta meningkatnya partisipasi aktif siswa dalam diskusi terkait isu-isu hukum. Integrasi pendekatan experiential learning dengan keterlibatan aktif mahasiswa sebagai fasilitator sejajar, yang menciptakan suasana pembelajaran hukum yang lebih egaliter dan kontekstual bagi siswa. Pendidikan hukum berbasis pengalaman langsung terbukti efektif dalam menanamkan kesadaran hukum secara kognitif, afektif, dan psikomotorik. Dengan demikian, pembinaan kesadaran hukum sejak dini melalui pendekatan partisipatif dapat menjadi fondasi membentuk generasi muda yang taat hukum dan berintegritas, sekaligus mendukung terwujudnya masyarakat yang adil dan tertib. Keberlanjutan program serupa sangat dianjurkan guna memastikan internalisasi nilai-nilai hukum secara konsisten.